Effects of carnauba wax and chitosan bilayer edible coating on shelf life of fresh-cut apple - Pestana, G. C.; Santos, K. A. F. dos; Miranda, M. [UNESP]; Spricigo, P. C.; Mitsuyuki, M. C.; Bresolin, J. D.; Hubinger, S. Z.; Assis, O. B. G.; Ferreira, M. D. (Int Soc Horticultural Science, 2021)
Edible coatings can be an alternative to extend shelf-life and preserve quality of fresh-cut fruits by forming a barrier that avoids physical and microbiological damages. Such coatings can be formed by individual or multiple layers. The main aim of this study consisted in the evaluation of the effect of a bilayer coating (carnauba wax and chitosan) on the quality of fresh-cut apples. Chitosan and carnauba wax were characterized, individually and in bilayer format, by Attenuated Total Reflectance (ATR). The tests were performed on apple cv. Gala, sliced and sanitized, in five different treatments: (T1) uncoated, taken as control; (T2) Ascorbic acid solution at 1%; (T3) Chitosan at 1.5%; (T4) Carnauba wax at 0.5% and (T5) Bilayer – (Chitosan 1.5% + Carnauba wax 0.5%). Physicochemical and microbial analyses were carried out every two days along 10 days storage at 5°C. Sensorial analyses were conducted on the fifth and tenth day. ATR revealed no interaction between main functional groups of carnauba wax and chitosan groups on the bilayer formations and no differences in firmness and weight loss were found among samples during the storage time. Color measurements confirmed that coated slices became dark faster than uncoated samples. Concerning microbiological analyses (total coliform microorganism and E. coli), slices coated with both chitosan and carnauba+chitosan bilayer, had the bacterial growing rate reduced. In sensorial analyses, panelists pointed their preference for apple slices treated with carnauba and also for bilayer coating, choice probably related to fruit appearance.
Keywords: Fruit quality; Microbiological analyses; Physic-chemical; Sensorial analyses